Developing the cost for uncomplicated scute st elevated myocardial infarction (Stemi primary percutaneous coronary intervention) using step down and activity based costing at UKMMC - Aniza I,; Syafrawati,; Saperi S,; Zafar M,; Amrizal MN,; Ika Fazura MN, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Background : Cardiovascular disease is the number one cause of death globally and is projected to remain the leading cause of death. If the trend is allowed to continue, by 2015 an estimated 20 million people will die from cardiovascular disease (mainly because of myocardial infarction and strokes). The number of cardiovascular disease cases in Malaysia has increased to 14% in five years from 96,000 cases in 1995 to 110,000 cases in 2000. Methods : The cost to treat patients admitted to Universiti Kebangsaan Malaysia Medical Center (UKMMC) Malaysia, diagnosed with Acute Uncomplicated ST Elevated Myocardial Infarction (STEMI) was calculated by using two different methodologies, namely step down costing methodology and activity based costing using clinical pathway. Result : Cost for each stay per day at the cardiology ward using the step down methodology is RM596.42. The treatment cost is estimated from RM1, 789.26 to RM 4,771.36. The average cost per episode for STEMI care with the average length of stay for 5.6 days is RM3, 340(SD ±596.42. The cost of coronary PCI procedure in step costing is RM 13,950.00. Hence, the total cost incurs for STEMI with PCI is RM 17,290.00(SD ±596.42) by using step down method. (an average cost per episode is RM3,340, plus the cost of coronary procedure of RM 13,950.00 . However by using the ABC the cost of STEMI (PCI) with an average length of stay for 5.6 days is RM 20,431.39. The study showed the ABC method was higher by 15.3% than the step down costing. Conclusion : The cost in managing STEMI (PCI) with the average length of stay of 5.6 days was calculated by using two different methodologies, namely step down costing methodology and activity based costing. Cost of treatment calculated by using activity based costing are higher because all resources used are incorporated in detail. The ABC method was higher by 15.3% than the step down costing. The difference is within 80-20 rules and the biggest percentage of cost in both methods is procedure or PCI cost.